APPLYING COLLABORATIVE GOVERNANCE AS AN INTERVENTION IN STUNTING REDUCTION An Empirical Community Empowerment Model in Sukabumi District - Novira, Alikha; Anomsari, Endah Tri; Pradesa, Hafid Aditya; Afandi, Muhamad (Department of Government, FISIP, Universitas Padjadjaran, 2024)
This research aims to formulate a community empowerment model to increase locals' capacity to engage more actively in collaborative governance. By using descriptive methods, qualitative approaches, and data collection using interviews, observations, and documentation, the focus and locus of this study limited to specific coverage area in Sukabumi Regency. Data analysis used an interactive model, and its finding reveals the community empowerment model which has implies consideration in the Community Empowerment Process, include the limitations of Community Participation, Volunteering, collective Regeneration, Empowerment, and action, and Increasing community capabilities. Stunting reduction is a part of regional development, while Sukabumi district is considered as an area that is an integral part of the government's hard efforts to fight stunting. Finding shown that development programs in stunting reduction require more involvement from the state and society. Increasing community participation can be encouraged by building community capabilities to participate more in collaborative processes.gb777